La participation, dans quel sens? L'exemple des organisations communautaires et de l'agriculture urbaine dans les villes de Mexico et de Cuernavaca - Boulianne, Manon (Anthropologica, 2022)
In accordance with a theory of social movements which puts emphasis on the symbolical dimensions of collective action, this article suggests that what participation means is at stake as community organizations are integrating in increasing numbers financial schemes directed at the development of popular entrepreneurship. In the context of the transformation of the urban popular movement in Mexico, the case of two community organizations which have recently developed urban agriculture activities directed at the market illustrates that this new situation induces, both for persons and the organizations they belong to, a renegotiation of the meaning of participation.